EKSISTENSI PERMAINAN TRADISI NGLARAK BLARAK DI KALURAHAN KRANGGAN KAPANEWON GALUR KABUPATEN KULON PROGO TAHUN 2023 - Silviani, Nindira Roku; Triwahan (Universitas PGRI Yogyakarta, 2023)
The aims of this study are (1) to ﬁnd out the origins of the Nglarak Blarak tradition in Kranggan Kapanewon Subdistrict, Galur, Kulon Progo Regency (2) To understand philosophy and development of the Nglarak Blarak tradition in Kranggan Kapanewon Galur Village Kulon Progo Regency (3) To understand and apply the tradition of Nglarak Blarak Di Kranggan Kapanewon Galur Village, Kulon Progo Regency. This study uses a method qualitative description analysis. Method The qualitative method is a method based on real events. qualitative have. When data collection using observation, interviews, documentation and literature study. In data analysis using techniques such as data editing, data presentation and veriﬁcation. The validity of the data uses discussions and triangulation. Based on the results of the study it can be concluded that (1) the Nglarak Blarak tradition is a traditional game originating from Kokap, Kulon Progo. The Nglarak Blarak tradition is one of the games from Kulon Progo Regency. The Nglarak Blarak tradition has another word, namely Nglabrak which has the meaning of coming to someone or something passionate about negative things such as poverty, stupidity. (2) The Nglarak Blarak tradition has very diverse philosophies such as avoiding negative things, mutual cooperation, all stages have their own stages, and so on. In the development of the Nglarak Blarak tradition, it is held every year on the birthday of Kulon Progo Regency. (3) The Nglarak Blarak tradition has a very interesting procession. In the traditional procession, the Nglarak Blarak must have a team consisting of 3 men and 3 women and a game of dragging using the fronds of a coconut tree. On tradition. So the tradition of Nglarak Blarak should not become extinct and the next generation can play the Nglarak Blarak game